Kontruksi Jilbab Dikalangan Mahasiswi (Studi Fenomenologi Mahasiswi Universitas Islam Indonesia Yogyakarta dalam Memaknai Jilbab) - marthalena, marthalena (Universitas Serang Raya, 2015)
This research is to discuss and to analyze about a background of the student of universitas islam indonesia yogyakarta to use headgear and their processes are objectivation, internalization and externalization processes. The research objective is to analyze about a backgruond of the students of universitas islam indonesia yogyakarta (UII) to use headger and to analyze how they are meaning of the headger their use. The benefit of this research is to give the contribution about of sosiology knowledge concerning headger phenomenon in education institution on the later to use for helping the next empirical research and this researh could to become consideration in making a wisdom that related with headger in UII. This research isi using Peter L Berger's of perspective theory, researcher want to know and to analyze the process of knowladge contruction about headger in student.